TYULMEN MICROBIOTA OF THE MIDDLE RIPHEAN OF THE SOUTHERN URALS - Yankauskas T.V.; Kozlova E.V.; Kozlov V.I. (My University, 1989)
The authors analyze a new Precambrian microbiota from the top of the Tyulmen beds that constitute the top of the Avzyan Formation of the Middle Ripean of the southern Urals. This microbiota is interesting for two reasons. First, it provides the first information on the microfossil composition of the youngest deposits of the Middle Riphean and thus complements previously available data on the distribution of microfossils in the stratotype sections of the Riphean. Second, together with previously available data on the microfossil content of the oldest deposits of the Upper Riphean of the Urals and Cis-Urals (Kabakov microbiota, it allows us to characterize changes in microfossil composition immediately at the transition from Middle to Upper Riphean deposits.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей